Community Participation on the Disaster Resilient Village Program in Pesanggrahan Kota Batu - Ruth Agnesia Sembiring; Derry Lorenza - (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2020)
The Pesanggrahan Head Village through the Decree of Pesanggrahan Head Village No: 141/84/422.310.7/2019 on June 26th, 2019 legitimized the DESTANA Program in Pesanggrahan Village which is community-based. The researcher analysis in community participation in the DESTANA Program uses the concept of forms of community participation by Cohen and Uphoff. This research is a descriptive qualitative research method using interview analysis technique, observation and documentation. Based on the observations results which have been performed by the researcher shows that there is FPRB SK on June 2019, which was not implemented properly due to the insistence of the Batu City BPBD in collaboration with the Pesanggrahan Head Village without a community involvement that only pursued the Batu City BPBD RENSTRA 2017-2022 target in the establishment of the DESTANA Program. The research results namely: (1) Community Participation in the decision-making process had 97% success of this program through community participation involved in the establishment of the FPRB that the target of BPBD in the establishment of the forum was 35 people, but in reality, only 32 people were involved in the forum. (2) Participation in the implementation of the community begins to abandon local wisdom and customs in coping with disasters. (3) Participation in the acceptance of the benefits has been evenly received by various elements of the Pesanggrahan Village community related to disaster education training. (4) Participation in the evaluation process has succeeded in optimizing the FPRB SK in June 2019 and was optimized in November 2019.